2002
DOI: 10.1074/jbc.m200805200
|View full text |Cite
|
Sign up to set email alerts
|

Apaf-1 Is a Mediator of E2F-1-induced Apoptosis

Abstract: E2F-1 is capable of promoting both cell cycle progression and apoptosis. The latter is important for suppressing untoward expansion of proliferating cells. In this study, we investigated its underlying mechanisms. E2F-1-induced apoptosis was accompanied by caspase-9 activation and inhibited by a specific inhibitor of caspase-9 in K562 sublines overexpressing E2F-1. E2F-1 enhanced the expression of Apaf-1 without the cytosolic accumulation of cytochrome c. Apaf-1-deficient melanoma cell lines were resistant to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(117 citation statements)
references
References 47 publications
7
110
0
Order By: Relevance
“…[6][7][8][9] In addition, Qin et al have also independently reported low Apaf-1 expression in metastatic melanoma cell lines used in our initial study. 12 These results, along with recent reports of low Apaf-1 expression in other melanoma cell lines, 13 are consistent with our initial findings.…”
supporting
confidence: 91%
“…[6][7][8][9] In addition, Qin et al have also independently reported low Apaf-1 expression in metastatic melanoma cell lines used in our initial study. 12 These results, along with recent reports of low Apaf-1 expression in other melanoma cell lines, 13 are consistent with our initial findings.…”
supporting
confidence: 91%
“…6,18,19 In our experiments using transient transfections, p53-deficient cells, as well as p53 siRNA, we could demonstrate that IKIP expression is dependent on p53 (Figure 7b, c and e). However, no regulation by E2F-1 could be observed (not shown).…”
Section: Discussionmentioning
confidence: 63%
“…From the variety of potential transcription factor binding sites (see Figure 7a), p53 and E2F-1 have been found to be functional and lead to increased APAF1 expression. 18,19 We therefore tested the p53 dependence of IKIP by transfecting a p53 expression vector into HEK 293 cells and analyzed IKIP expression by Western blotting using an antiserum generated against an N-terminal peptide of IKIP1. Transfection of p53, but not of NF-AT that was used as a negative control, increased IKIP1 protein levels in a dose-dependent manner (Figure 7b).…”
Section: Analysis Of the Common Apaf1/ikip Promoter Reveals Regulatiomentioning
confidence: 99%
“…Apaf-1 and caspase 7) directly, or by suppressing antiapoptotic signals such as the activation of NF-kB Perhaps more simple to understand are a number of reports that have recently implicated E2F-1 as being a regulator of factors intrinsic to the apoptotic process, for example, apoptosis protein-activating factor (Apaf-1). 71,72 When induced, Apaf-1 assembles with cytochrome c, a mitochondrial signal released on receipt of apoptotic signals, and activates caspase 9 leading to the activation of downstream effector caspases eventually leading to apoptosis (Figure 3). 73 Although the death receptor and the Apaf pathways can be thought of as distinct, there is accumulating evidence that crosstalk occurs between all the different pathways, so the complex pattern of signal interaction must first be determined before the effects of individual signals can be seen.…”
Section: A Role In Cancermentioning
confidence: 99%